The Dark Side Of Fast Fashion: Examining The Exploitation Of Garment Workers In Bangladesh - Yordan Gunawan; Anandiva Matahariza; Wiwit Kharisma Putri (Jurnal Hukum dan Peradilan, 2023)
There have been several attempts to decrease the usage of fast fashion, but no one has been able to stop its development. We are aware that fast fashion is a business model that imitates the most recent catwalk trends, has evolved into high fashion, is produced in large quantities, and is priced affordably. Fast fashion has come under fire from a wide range of people due to the fact that no worker receives the minimum wage, yet products must be mass-produced. In addition to examining the legal and regulatory framework for protecting Bangladesh garment industry workers to fulfill their rights as laborers and how these rights are applied, this article looks at the shadowy side of fast fashion in Bangladesh. This paper elaborates on Bangladesh's experience in managing the situation of a garment industry building that collapsed in 2013, killing hundreds of people inside, using a normative analysis-oriented approach. This study demonstrates that Bangladesh's legal and regulatory framework for worker protection has yet to explicitly state what rights workers are entitled to. Another factor is that Bangladesh does not yet have a robust and consistent practice of human rights-based instruments considered in court and that law enforcement does not fully grasp how to execute these rights. At the same time, it is crucial to improve law enforcement interpretation for worker-focused solutions, giving their rights, and promoting human rights practices in Bangladesh.